New insights into cell non-autonomous mechanisms of the C. elegans hypoxic response. Issue 2 (2nd April 2016) - Leiser, Scott F.; Rossner, Ryan; Kaeberlein, Matt
ABSTRACT: The hypoxic response is a well-studied and highly conserved biological response to low oxygen availability. First described more than 20 y ago, the traditional model for this response is that declining oxygen levels lead to stabilization of hypoxia-inducible transcription factors (HIFs), which then bind to hypoxia responsive elements (HREs) in target genes to mediate the transcriptional changes collectively known as the hypoxic response. 1, 2 Recent work in C. elegans has forced a re-evaluation of this model by indicating that the worm HIF (HIF-1) can mediate effects in a cell non-autonomous fashion and, in at least one case, increase expression of an intestinal hypoxic response target gene in cells lacking HIF-1.